EFEKTIVITAS PENGGUNAAN MEDIA PEMBELAJARAN VISUAL TERHADAP HASIL BELAJAR BIOLOGI SISWA MATERI STRUKTUR SEL KELAS XI IPA SMA NEGERI 5 PADANGSIDIMPUAN - Lastri Handayani Lubis (JURNAL EDUGENESIS, 2019)
The aims of this study is to describe the effectiveness of using visual learning media on students’ biology achievement on the topic cell structure at the eleventh grade students of SMA Negeri 5 Padangsidimpuan. This research was conducted by applying experimental (one group pre test post test design) with 37 students as the sample and they were taken by using cluster random sampling technique from 179 students. Observation and test were used in collecting the data. Based on descriptive analysis, it was found that: (a) the average of using visual learning media was 3.20 (good category) and (b) the average of students’ biology achievement on the topic cell structure before using visual learning media was 70.41 (good category) and after using visual learning media was 79.43 (good category). Furthermore, based on inferential statistics by using ttest, one tail, the result showed ttable was less than tcalculated (1.69 < 10.78). It means, there is a significant influence of using visual learning media on students’ biology achievement on the topic cell structure at the eleventh grade students of SMA Negeri 5 Padangsidimpuan.